2022
DOI: 10.1155/2022/2009894
|View full text |Cite|
|
Sign up to set email alerts
|

PRISM: A Novel Visual Instrument to Facilitate Self-Reflection and Learning Progress in Undergraduate Dental Education

Abstract: Objectives. PRISM (Pictorial Representation of Illness and Self-Measure) is a simple visual tool that has been successfully used as a visual metaphor in medicine. In this pilot study, PRISM was used for the first time to test its potential to support self-reflection and expectations of learning in dental students. Methods. Dental student volunteers (25 3rd year, 10 4th year, and 10 5th year) participated. Using both quantitative and qualitative methods, PRISM interviews were compared with a numerical scale in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is also work with social-constructivist view of collaboration with their classmates and the small group of teacher-students interaction. Fidelia (2015), Lew and Schimdt (2011) and Schmalz et al (2022) all suggest that self-reflection-based instruction has a positive effect on learners' essay writing achievement.…”
Section: Review Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It is also work with social-constructivist view of collaboration with their classmates and the small group of teacher-students interaction. Fidelia (2015), Lew and Schimdt (2011) and Schmalz et al (2022) all suggest that self-reflection-based instruction has a positive effect on learners' essay writing achievement.…”
Section: Review Literaturementioning
confidence: 99%
“…However, restricting reflection before action and in action in essay writing is not common to study. Attention to this neglect and engaging students in their real learning practice is needed (Edwards, 2017;Schmalz et al, 2022). One example of this is the effect of self-reflection on student learning.…”
Section: Self-reflection-based Instructionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%